Penerapan Model Problem Based Learning (PBL) Berbantuan LKPD QR-Code untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPAS Kelas V SD Negeri 1 Lalanglinggah - Indrayanti, Ni Kadek Dian; Arrang, Ni Luh Ayu Dwi Novita; Dewi, Ni Made Ratri Candra; Anwar, Khairil; Hasanah, Uswatun (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research is an implementation of the use of the Problem Based Learning (PBL) Learning Model assisted by LKPD QR Code as a form of innovation in the learning and teaching process. The aim of this research is to determine the improvement in student learning outcomes in science subjects using the PBL learning model assisted by LKPD QR Code. This research was carried out for 1 month starting from 26 July to 25 August 2023, on 19 class V students of SD Negeri 1 Lalalinggah. This research procedure was carried out in 2 cycles with research methods using quantitative methods. In the initial research, it was found that 13 students out of 19 students scored less than 65. However, in subsequent learning activities through the PBL learning model assisted by LKPD QR Code, student learning outcomes could be improved. This can be seen from the average score before treatment which was 57.63. Meanwhile in cycle I the average score of students increased to 62.00 and in cycle II the average score of students' abilities increased to 72.55.